2015
DOI: 10.1111/jgh.12967
|View full text |Cite
|
Sign up to set email alerts
|

Prospective population‐based cohort of inflammatory bowel disease in the biologics era: Disease course and predictors of severity

Abstract: A high rate of inflammatory disease, frequent immunomodulator use in CD, and a low rate of surgery in both CD and UC were identified. In CD, ileal involvement and complex disease behavior are associated with a more severe disease course, while in UC a high CRP predicted this outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 42 publications
(115 reference statements)
8
59
7
Order By: Relevance
“…This result is consistent with the observation from the previous study, although hospitalization itself cannot be compared between studies due to differences in medical environment between the studies [10]. In our study, Montreal B3 behavior and perianal disease at baseline were also significantly associated with subsequent CD-related hospitalization, which is consistent with an observation in a prospective population-based study in an Australian cohort [20]. The association between perianal disease and further hospitalization risk was also observed in the study by Click et al [10].…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the observation from the previous study, although hospitalization itself cannot be compared between studies due to differences in medical environment between the studies [10]. In our study, Montreal B3 behavior and perianal disease at baseline were also significantly associated with subsequent CD-related hospitalization, which is consistent with an observation in a prospective population-based study in an Australian cohort [20]. The association between perianal disease and further hospitalization risk was also observed in the study by Click et al [10].…”
Section: Discussionsupporting
confidence: 92%
“…CD hospitalisation rates were higher than UC (41.9% vs 19%), consistent with findings from the Barwon cohort (28% vs 17%) and European studies . However, unlike other studies, we found no association between ileocolonic location or penetrating behaviour and hospitalisation rates .…”
Section: Discussionsupporting
confidence: 87%
“…Gearry et al reported on IBD epidemiology in the Canterbury region of New Zealand in 2006 and 2014 . Wilson et al, Studd et al and Niewiadomski et al conducted similar research in the Barwon region of Victoria, Australia, between 2010 and 2016. These studies report epidemiological rates similar to Northern Europe and America, which are among the highest in the world.…”
Section: Introductionmentioning
confidence: 92%
“…Greenstein et al [4] described penetrating CD (PCD), characterized by acute perforation, chronic fistula or abscess formation, as a distinct aggressive type, which influences interval to reoperation. Recently, Niewadomski et al [5] showed that penetrating disease, although treated by modern immunosuppressive medication, is still associated with a more severe course of disease. Given that typical features of penetrating disease are established risk factors for postoperative complications and adverse short-term outcomes in surgery, the question arises whether minimal-invasive surgery is an appropriate approach for PCD [6, 7].…”
mentioning
confidence: 99%